Development of a Test Set Up for Characterization of Mixed-mode Fracture Toughness of Structural Adhesives - Soares, A.R.F.; Campilho , R.D.S.G. (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
The primary objective of this work is to design, numerically model and experimentally validate an MMB test equipment for structural adhesive tests, considering the study and critical analysis of existing equipment. The numerical work consists of creating the geometries of the different components of the equipment in software and carrying out the respective simulations for structural validation. Experimentally, the intention is to manufacture the designed equipment and carry out the respective tests. In real applications, adhesive joints are subjected to mixed mode I+II loading. The tests developed for mixed-mode loading are complex but considered highly relevant for fracture characterization. There are several mixed-mode tests, of which the Mixed-Mode Bending (MMB) test stands out for its capacity to allow the variation of the mixed-mode ratio practically without limitations. In this work, the main objective is to design, numerically model and experimentally validate an MMB test equipment to perform structural adhesive tests. Experimentally, it is intended to design and manufacture the MMB test equipment, and subsequently carry out the respective tests. The end result should be equipment that enables obtaining various mixed-mode combinations, using a single equipment and the same type of test specimen, for further application in the design of adhesively-bonded joints. The adhesive layer’s edge corresponded to the initial crack, the calibrated shim was composed of outer steel shims glued to a middle sharp blade, to produce a sharp crack for crack initiation. After the curing time of one week, the excessive adhesive was removed from the joints, one of the specimens’ sides was painted with white corrector fluid and a printed scale was glued at the same face to facilitate reading of crack length during the test. The equipment was validated by fabricating and testing adhesive joints, although further validation should contemplate estimating the mixed-mode behaviour of adhesive joints and comparing with literature data.